Services Via Mobility Portal for University Utara Malaysia - Almabhouh, Alaaeddin H A (2006)
The technology such as mobile has become an important medium for people to communicate between each other. This research used the Object Oriented Methodology (OOM) as a guideline. The goal of this research project is to develop Mobile Portal System for UUM Information Services using Wireless Application Protocol (WAP) technology that supports the use of smart phones devices for the benefit of the public. A brief overview of several mobile technologies is presented. The development process and problems encountered when designing the prototype of the Mobile Portal System is discussed in this paper. The usability testing conducted in this research revealed that the WAP site application is effective and should be implemented for UUM Mobile Portal System.